2021
DOI: 10.4103/jfmpc.jfmpc_2455_20
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pandemic (COVID-19) preparedness in a teaching hospital in northern India using available (CDC-Atlanta) checklist

Abstract: Background: Hospitals are at the forefront of dealing infectious public health emergencies. Recently, COVID-19 has been declared as pandemic by the World Health Organization. Dealing with COVID-19 pandemic requires high intensity of administrative activity. Objective: We conducted this study to assess and compare, objectively, hospital preparedness with available Centre of Disease Control and Prevention (CDC) standards. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Identifying and introducing the information cascade team to personnel and key individuals are emphasized in the discussion of “early warning,” as is determining the specific code of biological threats, identifying the process of confirming emergency operation center news and announcing new cases of the disease and the activation of HICS (through Systematic EEP, 2019; Sheikhbardsiri et al , 2018). In response planning and case management, early detection, warning and reporting of suspicious cases are critical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying and introducing the information cascade team to personnel and key individuals are emphasized in the discussion of “early warning,” as is determining the specific code of biological threats, identifying the process of confirming emergency operation center news and announcing new cases of the disease and the activation of HICS (through Systematic EEP, 2019; Sheikhbardsiri et al , 2018). In response planning and case management, early detection, warning and reporting of suspicious cases are critical.…”
Section: Discussionmentioning
confidence: 99%
“…In India, hospital preparedness during the COVID-19 pandemic assessed with available centre of disease control and prevention standards. In this survey, the programs, care processes and specific facilities required to deal with the COVID-19 pandemic were evaluated (Singh et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Labib et al, which examined the preparedness of special wards in Egyptian hospitals, the mean preparedness score was 54%, which showed that the preparedness was moderate [19]. In the study by Singh et al, which examined the preparedness of a teaching hospital in northern India, the mean score in the areas of preparation against the COVID-19 pandemic was 72.96% [21].…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Labib et al, the highest score in the area of preparedness belonged to support and logistics management, and the lowest score to the areas of human resources and information [19]. In the Singh et al study, the highest preparedness score belonged to the structure of planning and decision making [21]. In the Dewi et al study, the highest scores in the private and public hospitals belonged to the field of management in designing programs for COVID-19.…”
Section: Dewi Et Al's Study On Three Indonesian Hospitalsmentioning
confidence: 97%
See 1 more Smart Citation